The use of collagen type-II as an indicator for assessment regeneration effect post intra-articular pure-PRP injection in KOA patient - Alzamily, Ajil; Jifeel, Waleed (Journal of Biomedicine and Biochemistry, 2022)
Background: knee osteoarthritis (KOA) is a complex disease that causes metabolic, structural, biochemical, and functional alterations in afflicted tissues. Physical examination and radiological findings are the present methods for the diagnosis of knee osteoarthritis. Traditionally, KOA medication focused on symptom management. Clinical trials focused on delaying or reversing disease development have gained popularity in recent years. PRP is among the medicinal approaches used to manage KOA.Purpose: By assessing the cartilage degradation marker collagen-II, the study's aim was to figure out whether the use of pure-PRP may help KOA patients' damaged cartilage layers regenerate.Methods: This non-randomized controlled trial study involved 66 patients with knee OA and 28 healthy control subjects from December 2021 to February 2022. There were 2 categories of knee OA patients: 34 with moderate (grade-3) and 32 with mild (grade-2) KOA. So, every group of KOA patients is divided into three subgroups based to the frequency of injections (single, double, or triple) in addition to severity. Based on clinical and radiological data using the Kellgren-Lawence (KL) 0–4 grading system, the patients' diagnoses and classifications are made. This study was designed at AL-Imam Ali hospital, Babylon governorate, Iraq and approved by the medical human research ethics committee at Al-Qadisiyah university/ collage of medicine.Results: The findings of this investigation show that the serum collagen type-II content was considerably greater in KOA patients were compared to control subjects, and in moderate compared to mild KOA as the severity of the disease progressed. But following pure-PRP injection, the serum level of collagen type-II did not significantly decrease, and increasing the number of injections had no better effect.Conclusions: PRP therapy was generally acceptable for patients in terms of improving symptoms and there were no complications following injection. However, there is insufficient indication that platelet rich plasma regenerates cartilage damage in knee OA patients, as there was no significant decrease in the amount of collagen type-II.